Effectiveness of Grounded Sleeping on Recovery After Intensive Eccentric Muscle Loading - Müller, Erich; Pröller, Patrick; Ferreira-Briza, Fatima; Aglas, Lorenz; Stöggl, Thomas (Frontiers in Physiology, 2019)
Purpose: We set out to investigate the effectiveness of grounded sleeping on the time course of recovery with respect to muscle soreness and athletic performance after intensive eccentric muscle loading. Methods: Twenty-two healthy participants were recruited for this study and randomly assigned to an experimental group (GRD, grounded sleeping, n = 12) or control group (UGD, sham-grounded sleeping, n = 10) to evaluate the effects of 10 days recovery with GRD vs. UGD following a single intensive downhill treadmill intervention in a triple-blinded (participant, tester and data analyst) manner. To operationalize recovery a test battery was performed at baseline and on days 1, 2, 3, 5, 7 and 10 post-intervention: 1) perception of muscle soreness (VAS), 2) creatine kinase blood levels (CK), 3) maximum voluntary isometric contraction (MVIC) for both legs, 4) counter movement jump (CMJ) and drop jump (DJ) performance. Furthermore, in four participants blood was sampled for detailed analysis of complete blood counts and serum-derived inflammation markers. Results: The downhill treadmill running intervention led to distinct changes in all measured parameters related to fatigue. These changes were detectable already 5-min post intervention and were not fully recovered 10 days post intervention. GRD led to less pronounced decrease in performance (CMJ, MVIC) and less increase with respect to CK compared with UGD (all P<0.05). Detailed blood samples demonstrated that grounded sleeping modulates the recovery process by a) keeping a constant hemoconcentration, as represented by the number of erythrocytes, and the hemoglobin/hematocrit values; and b) by the reduction of muscle damage-associated inflammation markers such as, IP-10, MIP-1α and sP-Selectin. Conclusion: The downhill running protocol is a feasible methodology to produce long term muscle soreness and muscular fatigue. GRD was shown to result in faster recovery and/or less pronounced markers of muscle damage and inflammation. GRD might be seen as a simple methodology to enhance acute and long-term recovery after intensive eccentric exercises.